Interpretation of an Epoch in the Novel "the Big Green Tent" by L. Ulitskaya: Linguistic-Cultural Analysis of Verbal Lexicon - Safin, Ildar Ch.; Kolosova, Elena I.; Gimranova, Tatyana A. (Journal of History Culture and Art Research, 2017)
This article is the verbal lexicon analysis based on the text of the novel "The Big Green Tent" by L. Ulitskaya. The creative manner of the contemporary writer attracts the attention of researchers, her writings describe the emotional experiences of the heroes and also give a generalized image of time full of historical details and features. The language of her stories and short stories is characterized by a special style in the description of time realities. A verb in the text allows the author to express the events and the circumstances that characterize an action in its dynamics due to the fact that verbal categories reflect the real reality in our consciousness. The method of linguistic cultural analysis of verbal lexicon in the novel "The Big Green Tent" made it possible to single out exactly those language units that the writer carefully selects for the creation and interpretation of the era. A special emphasis in the study is made on the creation of an expressive-emotional style of narration using the stylistic capabilities of the Russian verb. The individual author’s methods of narration expressiveness creation are singled out: synonymous series, euphemisms, colloquial lexicon, etc. The conducted study and a careful analysis of the selected factual material testifies that, recreating an epoch, the master of the word invariably uses that language arsenal that brightly and fully conveys the color of time. L. Ulitskaya is able to be not only an indifferent witness of the epoch, but also her tenacious observer and interpreter. The analyzed factual material and the main points of this research can be used in the courses on stylistics and linguistic culturology, and also as an illustrative material during the classes on the linguistic analysis of a literary text.